2013
DOI: 10.1016/j.ijscr.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Surgically proved visually isoattenuating pancreatic adenocarcinoma undetected in both dynamic CT and MRI. Was blind pancreaticoduodenectomy justified?

Abstract: When the above studies fail to unmask the lesion, blind pancreaticoduodenectomy should be based on strong clinical suspicion and secondary imaging findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Because pancreatic cancer frequently has an abundant fibrotic stroma, which is seen as a hypo-attenuating mass in the early arterial phase with progressive delayed enhancement 29 , 30 , we believe that the lower average observed on the pancreas phase images reflects pancreatic cancer with abundant desmoplastic reactions. Other studies have suggested that iso-attenuating pancreatic cancers on early-phase images tend to display less desmoplastic change within the mass and show better survival outcome 25 , 31 – 36 . Studies involving diffusion MRI have concluded that the degree of fibrosis in pancreatic cancer cases correlates with diffusion restrictions related to poor prognosis 37 , 38 and that it could be used to monitor treatment response 39 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because pancreatic cancer frequently has an abundant fibrotic stroma, which is seen as a hypo-attenuating mass in the early arterial phase with progressive delayed enhancement 29 , 30 , we believe that the lower average observed on the pancreas phase images reflects pancreatic cancer with abundant desmoplastic reactions. Other studies have suggested that iso-attenuating pancreatic cancers on early-phase images tend to display less desmoplastic change within the mass and show better survival outcome 25 , 31 – 36 . Studies involving diffusion MRI have concluded that the degree of fibrosis in pancreatic cancer cases correlates with diffusion restrictions related to poor prognosis 37 , 38 and that it could be used to monitor treatment response 39 .…”
Section: Discussionmentioning
confidence: 98%
“…One of characteristic pathologic features of pancreas cancer is the presence of intense fibrosis in the tumor, which is known as desmoplastic reaction 21 . Previous studies have demonstrated that scirrhous carcinomas with abundant fibrosis and relative sparse tumor cells in the stomach, bile duct, breast, and colon have a poor prognosis 22 – 25 . Now the evidence is accumulating that the fibrous component of a tumor correlates with its malignant behavior and contribute to therapeutic resistance 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Multi-detector computed tomography (MDCT), during the phase of peak pancreatic enhancement (pancreatic parenchymal phase) has high diagnostic sensitivity for visualizing PDA >2 cm, but decreases in smaller lesions [2]. These small, sometimes isoattenuating, lesions may only demonstrate subtle secondary features such as pancreatic atrophy or pancreatic or biliary ductal dilation and therefore can be difficult to visualize and consequently manage [3, 4]. Such isoattenuating lesions are not infrequent on MDCT.…”
Section: Introductionmentioning
confidence: 99%
“…Although MR imaging is more vulnerable to the effect of motion and usually has lower spatial resolution than CT, its strength lies in its high-contrast resolution that is potentially useful for evaluating low-contrast SPLs ( 10 11 12 13 ). With recent advances in MRI technology, including higher field strength (3T), increasingly powerful multichannel coils, high resolution three-dimensional (3D) gradient-recalled echo (GRE) sequences and diffusion-weighted imaging (DWI), MRI may provide improved diagnostic accuracy for SPLs than before ( 14 15 16 ).…”
Section: Introductionmentioning
confidence: 99%